Detrusor underactivity is the main reason for persistent symptoms after transurethral resection of the prostate - Esther Martinez-Cuenca; Miguel Á. Bonillo; Eduardo Morán; Salvador Arlandis (Continence Reports)
Introduction:: Transurethral resection of the prostate has been considered the gold standard for surgical management of benign prostatic enlargement. Despite its high success rate, a percentage of patients (20%–40%) do not improve afterward. Our purpose is to determine the underlying lower urinary tract dysfunction of patients with persistent symptoms after transurethral resection of the prostate (TURP). Material and methods:: We queried our prospectively maintained database to identify male patients with lack of symptoms improvement after TURP for benign condition. Patients with neurological condition and prostate cancer were excluded.Evaluation included symptoms assessment, prostate volume, uroflowmetry, maximum cystometric capacity, bladder compliance, detrusor overactivity and urodynamic stress urinary incontinence. We considered obstruction if Bladder Outlet Obstruction Index (BOOI) ≥ 40, no obstruction if BOOI < 20. We considered detrusor underactivity if Bladder Contractility Index (BCI) < 100. Results:: 219 patients had complete urodynamic study. Complete data were obtained from 107 patients, the mean (SD) age was 65.6 (8.2) years. Median (IQR) prostatic volume was 40 (31)cc. After surgery, storage symptoms were the most prevalent (73.8% of the patients). Urodynamic findings were: detrusor underactivity in 75 of 107 patients (70.1%), detrusor overactivity in 54 (50.5%), obstruction in 26 (24.3%).The only correlation found was between the pre-surgery voided volume in uroflowmetry and detrusor overactivity in the urodynamic study (rho: −0.28, p = 0.033). No difference regarding Qmax before and after TURP was observed in the detrusor underactivity group (p = 0.481). Unfavorable outcome after previous prostate surgery might be explained by detrusor underactivity rather than obstruction. Conclusions:: The most common persistent symptoms after TURP are storage, and the most common urodynamic finding is detrusor underactivity. In this scenario urodynamic study is advisable.